Fatty acid modification of Wnt1 and Wnt3a at serine is prerequisite for lipidation at cysteine and is essential for Wnt signalling - Doubravska, Lenka; Krausova, Michaela; Gradl, Dietmar; Vojtechova, Martina; Tumova, Lucie; Lukas, Jan; Valenta, Tomas; Pospichalova, Vendula; Fafilek, Bohumil; Plachy, Jiri; Sebesta, Ondrej; Korinek, Vladimir (Cellular signalling, 2011)
The Wnt family of proteins is a group of extracellular signalling molecules that regulate cell-fate decisions in developing and adult tissues. It is presumed that all 19 mammalian Wnt family members contain two types of post-translational modification: the covalent attachment of fatty acids at two distinct positions, and the N-glycosylation of multiple asparagines. We examined how these modifications contribute to the secretion, extracellular movement and signalling activity of mouse Wnt1 and Wnt3a ligands. We revealed that O-linked acylation of serine is required for the subsequent S-palmitoylation of cysteine. As such, mutant proteins that lack the crucial serine residue are not lipidated. Interestingly, although double-acylation of Wnt1 was indispensable for signalling in mammalian cells, in Xenopus embryos the S-palmitoyl-deficient form retained the signalling activity. In the case of Wnt3a, the functional duality of the attached acyls was less prominent, since the ligand lacking S-linked palmitate was still capable of signalling in various cellular contexts. Finally, we show that the signalling competency of both Wnt1 and Wnt3a is related to their ability to associate with the extracellular matrix.
Keywords: Amino Acid Substitution; Cysteine; Humans; proteiny Wnt; Wnt1 Protein; Wnt3 Protein; embryonální vývoj; serin; lipoylace; proteiny Xenopus; Molecular Sequence Data; molekulární sekvence - údaje; mutace; Lipoylation; Wnt Proteins; krysa rodu Rattus; protein Wnt3A; lidé; protein Wnt3; zvířata; Xenopus; myši; Wnt3A Protein; cystein; Xenopus Proteins; Mice; buněčné linie; Amino Acid Sequence; Embryonic Development; Cell Line; substituce aminokyselin; Rats; Animals; Mutation; protein Wnt1; Serine; sekvence aminokyselin